A novel active damping control based on grid-side current feedback for LCL-filter active power filter. (December 2020) - Gao, Tingting; Lin, Yanqiang; Chen, Dongdong; Xiao, Long
Abstract: LCL filter is widely used in grid-connected converters for good harmonic mitigation performance. However, resonance poles of LCL filter challenge system stability, especially in a digital control system. This paper studies the suppression method of the active power filter output LCL filter resonance. Because of the defect that the traditional active damping based on the filter capacitor current or capacitor voltage feedback needs to add additional sensors, a novel active damping with grid-side current component feedback is proposed. And analysis and design of the feedback function, the resonance suppression characteristics, and the impact on harmonic compensation performance are analyzed in detail respectively and proposes a novel active damping control method based on a quasi-resonant controller grid-side current feedback. On this basis, a mathematical model of the SAPF system with the proposed novel active damping was established, and the resonance characteristics were analyzed. Finally, the proposed method was verified through relevant experiments.